Variable Baseline Papio cynocephalus Endogenous Retrovirus (PcEV) Expression Is Upregulated in Acutely SIV-Infected Macaques and Correlated to STAT1 Expression in the Spleen - Maze, Emmanuel Atangana; Ham, Claire; Kelly, Jack; Ussher, Lindsay; Almond, Neil; Towers, Greg J.; Berry, Neil; Belshaw, Robert (Frontiers in Immunology, 2019)
Retroviral replication leaves a DNA copy in the host cell chromosome, and over millions of years such infection of germline cells has led to our genome sequence containing ~100,000 endogenous retrovirus (ERV) loci. Over time these loci have accrued mutations such as premature stop codons that prevent continued replication. However, many loci remain transcriptionally and translationally active today and ERVs have been implicated in interacting with the immune system. Using archived plasma and tissue samples from past experiments where macaques were infected with simian immunodeficiency virus (SIV), we explored how the expression of one of the macaque ERVs responded to viral infection and whether this expression correlated with a measure of the innate immune response. Specifically, we measured the RNA levels of (a) an ERV (Papio cynocephalus Endogenous Retrovirus, PcEV), (b) a key gene in the interferon signalling pathway (STAT1) and (c) the exogenous pathogen (i.e. SIV). Bioinformatic analysis of the DNA sequences of the PcEV loci within the macaque reference genome sequences was consistent with potential protein expression but not ERV replication. However, quantitative RT-PCR analysis of DNase-treated RNA extracts from plasma derived from acute SIV-infection indicated PcEV RNA in 7 animals. PcEV expression was elevated by SIV infection in all tissues. Moreover, tissue PcEV and STAT1 RNA expression levels were correlated during acute SIV infection (Spearman correlation r=0.47; p-value=0.0091), especially in the spleen, but STAT1 levels were not correlated to either tissue or plasma SIV RNA levels. We speculate that intracellular PcEV RNA expression and induction of a key component of the interferon cascade are causally linked.